FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI - Basuki, Ferry Hendro; Sososutiksno, Christina (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, 2022)
This study aims to empirically prove the influence of company size, profitability (NPM), board of commissioners size, and audit committee size on Corporate Social Responsibility disclosures in pharmaceutical companies listed on the IDX. The population in this study are all pharmaceutical companies listed on the IDX in 2013-2018. The research sample was taken based on a purposive sampling model, where the sample was selected with specific criteria that had been set. The data source was obtained from the annual report of pharmaceutical companies listed on the Indonesia Stock Exchange from 2013-2018. The data analysis method uses multiple linear regression analysis using the SPSS 21 software. Based on the research, results show that the size of the company and the size of the board of commissioners significantly affect the disclosure of Corporate Social Responsibility. Meanwhile, profitability (NPM) and the size of the audit committee have no impact on the disclosure of Corporate Social Responsibility.